Early childhood parenting in the review of Islamic religious perspectives in Songgom Brebes - Dedi Romli Triputra (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
This research aims to determine the form of foster pattern that parents applied to early childhood in instilling good behavior in accordance with the Islamic religion in TK. Pertiwi Songgom village District Brebes of Central Java. The method used in this research is a qualitatively descriptive method. The results of this study showed that the implementation of parenting patterns in educating religion in early childhood in Songgom is carried out by familiarizing the religious behavior by working on the five-time prayers, telling his son to ask, apply the child to behave politely. The factors influencing the foster pattern applied by parents in educating early childhood in Songgom village are the background of parenting patterns of parents, gender, culture, socio-economic status, education, family and living environment.